Fluid Neutral Model for Use in Hybrid Neutral Simulations of a Detached Case. Issue 6 (13th July 2016) - Horsten, N.; Dekeyser, W.; Samaey, G.; Börner, P.; Baelmans, M.
Abstract: Two fluid neutral models are compared with a finite volume solution of the kinetic neutral equation for a simplified 1D detached case. The neutral equations are coupled to the plasma equations. The first fluid neutral model assumes that neutral and ion temperature are equal while the second adds a separate neutral energy equation. It is illustrated that both the AMJUEL‐HYDHEL databases and TRIM code can be incorporated. The first model is already accurate giving a maximum relative error of 10% for the target fluxes. Adding an energy equation further decreases this maximum relative error to 5%.